Metastatic Peripheral Neuroblastoma in a Dog - Sayeg, Fernando Fernandes; Oliveira, Mariana Correia; Neves dos Santos, Bartolomeu Benedito; d'Ávila, Mariana Siqueira; Costa, Thiago Souza; Fernandes, Júlio Israel; de Andrade, Max Ferreira; Nogueira, Vivian de Assunção (Acta Scientiae Veterinariae, 2019)
Background: Peripheral neuroblast neoplasms are considered as a group of tumors derived from primitive cells of the neural crest that are progenitors of the sympathetic ganglia and adrenal medulla. Reports of neuroblastoma in dogs are scarce in English literature, and there are no reports from Brazil due to its rare occurrence or missed diagnosis, because modern techniques are often not accessible in Brazil. The aim of the present study was reported a case of metastatic peripheral neuroblastoma in a 10-month-old bitch of Canadian Shepherd breed, attended at the Small Animal Veterinary Hospital of the Federal Rural University of Rio de Janeiro (HVPA-UFRRJ). Case: A 10-month-old female dog, Canadian Shepherd breed, presenting prostration, inappetence, emesis, progressive weight loss, and difficulties in the locomotion of the pelvic limbs was brought to the Small Animal Veterinary Hospital of the Federal Rural University of Rio de Janeiro (HVPA / UFRRJ) for treatment. Palpation of the abdominal cavity revealed a mass of approximately 14.0 cm diameter in the thoracolumbar region. After the second visit to HVPA/ UFRRJ, there was worsening of the clinical condition and onset of pain and dyspnea; hence, euthanasia was performed. The dog was referred for necropsy; the examination revealed a mass measuring 40.0 × 35.0 cm in the abdominal cavity that caused displacement of the intestines and compressed the liver against the diaphragm, as well as another mass that traversed the diaphragm through the esophageal hiatus and surrounded the esophagus, aorta, and caudal vena cava. The right adrenal gland was compressed and adhered to the mass, and the left adrenal gland was not visualized. Specimens of various organs were collected, fixed in 10% buffered formalin, and processed according to routine histological technique. Immunohistochemical examination performed on mass specimens revealed positivity for the anti-CD56, anti-synaptophysin, anti-GFAP, and anti-NSE markers and negativity for the anti-chromogranin and anti-Olig2 markers. Based on pathology and immunohistochemistry findings, a diagnosis of poorly differentiated peripheral neuroblastoma was made; in addition, presence of emboli of neoplastic cells in the hepatic sinusoids and branches of the portal vein and metastasis in the spleen, lymph nodes, lung, and meninges were confirmed. Discussion: Positive results for neural markers associated with negative results for those of other small round cell tumors was considered to indicate the presence of neuroblast tumors; glioblastoma and oligodendroglioma were ruled out based on the absence of anti-Olig2 labeling, and, especially, the possibility of occurrence of pheochromocytoma was excluded based on the absence of anti-chromogranin. During necropsy, the location of the mass at the retroperitoneal space near the thoracolumbar junction, craniomedially in relation to the left kidney, was confirmed, which is compatible with the location of the adrenal gland. Metastasis in the dura mater was determined to be present based on necropsy findings alone, and neoplastic invasion through the esophageal hiatus of the diaphragm of a large part of the thoracic cavity was observed, which, to the best of our knowledge, have not been described in reports of veterinary medicine. The high rate of tumor growth and compression and invasion of adjacent tissues and organs may be considered as potential factors for unfavorable prognosis of peripheral neuroblastoma.